Biochemical and genetic analyses of the oomycete Pythium insidiosum provide new insights into clinical identification and urease-based evolution of metabolism-related traits - Krajaejun, Theerapong; Rujirawat, Thidarat; Kanpanleuk, Teerat; Santanirand, Pitak; Lohnoo, Tassanee; Yingyong, Wanta; Kumsang, Yothin; Sae-Chew, Pattarana; Kittichotirat, Weerayuth; Patumcharoenpol, Preecha (PeerJ, 2018)
The oomycete microorganism, Pythium insidiosum, causes the life-threatening infectious condition, pythiosis, in humans and animals worldwide. Affected individuals typically endure surgical removal of the infected organ(s). Detection of P. insidiosum by the established microbiological, immunological, or molecular methods is not feasible in non-reference laboratories, resulting in delayed diagnosis. Biochemical assays have been used to characterize P. insidiosum, some of which could aid in the clinical identification of this organism. Although hydrolysis of maltose and sucrose has been proposed as the key biochemical feature useful in discriminating P. insidiosum from other oomycetes and fungi, this technique requires a more rigorous evaluation involving a wider selection of P. insidiosum strains. Here, we evaluated 10 routinely available biochemical assays for characterization of 26 P. insidiosum strains, isolated from different hosts and geographic origins. Initial assessment revealed diverse biochemical characteristics across the P. insidiosum strains tested. Failure to hydrolyze sugars is observed, especially in slow-growing strains. Because hydrolysis of maltose and sucrose varied among different strains, use of the biochemical assays for identification of P. insidiosum should be cautioned. The ability of P. insidiosum to hydrolyze urea is our focus, because this metabolic process relies on the enzyme urease, an important virulence factor of other pathogens. The ability to hydrolyze urea varied among P. insidiosum strains and was not associated with growth rates. Genome analyses demonstrated that urease- and urease accessory protein-encoding genes are present in both urea-hydrolyzing and non-urea-hydrolyzing strains of P. insidiosum. Urease genes are phylogenetically conserved in P. insidiosum and related oomycetes, while the presence of urease accessory protein-encoding genes is markedly diverse in these organisms. In summary, we dissected biochemical characteristics and drew new insights into clinical identification and urease-related evolution of P. insidiosum.
Keywords: Pythiosis; Pythium insidiosum; Biochemical feature; Urease; Evolution; Identification; Biochemical test